Computational Metabolomics Reveals the Potential Mechanism of Matrine Mediated Metabolic Network Against Hepatocellular Carcinoma - Wang, Kexin; Ye, Xiangmin; Yin, Chuanhui; Ren, Qing; Chen, Yupeng; Qin, Xuemei; Duan, Chuanzhi; Lu, Aiping; Gao, Li; Guan, Daogang (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) is a complex issue in cancer treatment in the world at present. Matrine is the main active ingredient isolated from Sophora flavescens Air, possesses excellent anti-tumor effects in HCC. However, the specific underlying mechanisms, especially the possible relationships of anti-HCC effect of matrine and related metabolic network of HCC, are not yet clear and need further clarification. In this study, an integrative metabolomics-based bioinformatics algorithm was designed to explore the underlying mechanism of matrine on HCC by regulating metabolic network. Cell clone formation, invasion, and adhesion assay were utilized in HCC cells to evaluate the anti-HCC effect of matrine. Cell metabolomics approach based on LC-MS was used to obtain the differential metabolites and metabolic pathways regulated by matrine. Maximum activity contribution score (MACS) model was developed and applied to calculate high contribution target genes of matrine, which could regulate metabolic network based on co-expression matrix of matrine-regulated metabolic genes and targets. Matrine significantly repressed the clone formation and invasion, enhanced cell-cell adhesion, hampered cell-matrix adhesion in SMMC-7721 cells. Metabolomics results suggested that matrine markedly regulated the abnormal metabolic network of HCC by regulating the level of choline, creatine, valine, spermidine, 4-Oxoproline, D-(+)-Maltose, L-(-)-Methionine, L-Phenylalanine, L-Pyroglutamic acid, pyridoxine, which involved in D-Glutamine and D-glutamate metabolism, glycine, serine and threonine metabolism, arginine and proline metabolism, etc. Our proposed metabolomics-based bioinformatics algorithm showed that matrine regulating metabolic network exhibit anti-HCC effects through acting on MMP7, ABCC1, PTGS1, etc. Finally, MMP7 and its related target β-catenin were validated. Together, metabolomics-based bioinformatics algorithm reveals the effects of matrine regulating metabolic network in treating HCC relying on the unique characteristics of multi-targets and multi-pathways of traditional Chinese medicine.